Investigating the effect of training on the burden of cancer patients caregivers - Shahsavani, Alireza; Kiani, Fatemeh (International Journal of Psychosocial Rehabilitation, 2020)
Due to the cancer debilitating nature and its especial treatments the patients need help from their families but they usually have not enough knowledge to take care of these patients. Their role is very effective; it not only affects the physical care dimensions but also the psychological ones of the patients because they are the ones providing emotional and social support for the patients. Therefore, it is of great importance to promote the mental health of cancer patients’ caregivers who are under caregiving pressure therefore, this study aimed to examine the effect of training on the cancer patients’ caregivers’ burden. It is a semi experimental study. One hundred cancer patients’ caregivers who had the inclusion criteria were selected by random sampling method from Khatam Al Anbia and Ali Ibn Abitaleb hospitals. After having allocated patients into two groups of control and case control, at first before the intervention the caregivers filled out the caregiving pressure questionnaire in both groups and the control group only had the routine cares. Intervention included strategies of crisis management and stress that was done in the case group during five group sessions one time per week moreover its follow up took six weeks. after these periods, control and the case control groups received the questionnaires in addition post-test was carried out. SPSS version 21 was used to analyze the data and the significance level was considered 0.05. Results of this study showed that the mean and the SD of cancer patients caregivers age had been (34.68+- 11.48) and (37.08+-11.58) in case control and the control group respectively. They have also been (10.90) and (12.86) in case control and the control group regarding the disease duration. Considering the education, 68% of the patients in case-control group had a higher education than high school diploma and it was 32% for control group. Results showed that providing an instructional plan does not have impressive effect on caregiving burden thus it alone cannot be an effective method for reducing caregiving burden. It can be used in medical centers to maintain and promote the caregivers mental health but reducing caregiving burden also needs other solutions.